THE USE OF SCAFFOLDING STRATEGY IN TEACHING READING COMPREHENSION AT THE FIRST GRADE STUDENTSOF SMA N 4 MATARAM IN ACADEMIC YEAR2017/2018 - Patmah Siswanti; Rima Rahmaniah (Universitas Muhammadiyah Mataram, 2018)
Abstract: Scaffolding is a teaching learning strategy in which the teacher and learners engage in a collaborative problem-solving activity with the support and guidance of the teacher to enable learners become increasingly independent. Scaffolding strategy can help students solved the task by their own and student can be understand the material. The purpose of this research is to know whether the use of scaffolding strategy is effective or not in teaching reading comprehension at the first grade students of SMA N 4 Mataram in academic year of 2017/2018. This study used Quasi Experimental Non-Equivalent Control Group Designs, the researcher was used pre-test and post-test. The sample of this research were all students of the first grade at SMAN 4 Mataram that consist of 78 students, 39 students of experimental group and 39 students of control group. The experimental group was taught by scaffolding strategy in teaching reading comprehension and the control group was taught without scaffolding strategy in teaching reading comprehension. The techniques of collecting data in this research used pre-test and post-test. Based on the result, the means score of students experimental group was 23,17 and the control group was 16,70. It was shows that score of experimental group was higher than control group. Whereas, the score of t-test was 2,70 and the score of t-table was 2,00 on the level of significance 0,05. this research shows that scaffolding strategy in teaching reading comprehension at the first grade students of SMAN 4 Mataram in Academic Year 2017/2018 is effective. So, based on the hypothesis that the researcher discussed before, the Alternative Hypothesis (Ha) was accepted.